Infectious Disease and Imperfections of Self-Image. (February 2018) - Ackerman, Joshua M.; Tybur, Joshua M.; Mortensen, Chad R.
Infectious disease is an ever-present threat in daily life. Recent literature indicates that people manage this threat with a suite of antipathogenic psychological and behavioral defense mechanisms, which motivate the avoidance of people and objects bearing cues to pathogen risk. Here, we demonstrate that self-image is also impacted by these mechanisms. In seven studies, pathogen cues led individuals chronically averse to germs to express greater concern about their own physical appearance. Correspondingly, these people exhibited behavioral intentions and decisions intended to conceal or improve their appearance, such as purchasing facial products, taking pharmaceuticals, and undergoing cosmetic surgery. This work opens a new area of investigation for infectious-disease psychology research and highlights the central role played by physical appearance in pathogen-related cognition.